Technology system based on the 5W communication model: a review of computational communication technologies - WANG Xupeng; He Hongbo; WANG Runqiang (大数据)
Massive data and artificial intelligence technology provide great convenience for communication research, which can effectively solve the problem of communication effect measurement. Existing research in this field mainly focuses on the research paradigm, scenario application and development path of computational communication, and lacks the sorting and categorization of novel computational methods in computational communication. This paper adopts the literature research method, proposes a framework for categorizing computational methods based on the 5W communication model, and systematically compiles the new computational methods in the communication process with the goal of improving the communication effect, describing the ideas of the different computational methods, the required data sets and the evaluation methods. This paper analyzes the challenges faced by computational communication technology and looks forward to possible future research directions.